Meningkatkan Hasil Belajar Shooting dalam Permainan Sepak Bola melalui Model Pembelajaran Team Assisted Individualization (Tai) pada Siswa Kelas X MIA 1 SMA Negeri Ambon - Petra Thenu; Hasbullah, Bahmid; Mesak Hattu (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The game of football is one of the PJOK learning materials that is taught at every level of the education unit, both from elementary school to tertiary level. The purpose of this study was to determine the increase in shooting learning outcomes through the TAI learning model. This type of research is Classroom Action Research (CAR). The results of this study indicate that the results of the action in cycle I, there were 11 students who had completed or 74.75% with a total value of 884.5, 6 students did not complete or 25.24% with a total value of 298.7. In Cycle II, there were 17 students who completed with a total score of 1354.3 or 889.36%. There is an increase in learning outcomes of 13.89%, meaning that learning outcomes in shooting in soccer games can be improved through the TAI (Team Assisted Individualization) learning model.